2005
DOI: 10.3349/ymj.2005.46.5.679
|View full text |Cite
|
Sign up to set email alerts
|

The Regulators of VEGF Expression in Mouse Ovaries

Abstract: The objectives of this study were to explore whether ovarian vascular endothelial growth factor (VEGF) expression in mice can be regulated by IL-6 (interleukin-6), angiotensin II, FSH, and hCG; and to test whether the mouse ovarian VEGF expression can result in angiogenesis. The ICR mice were sacrificed, and their ovaries were recovered. Recovered ovaries were treated with IL-6, angiotensin II, FSH, and hCG separately and incubated for 24 hours in α-MEM. Expression of mRNA and protein of VEGF were assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
1
14
0
2
Order By: Relevance
“…In the ovary, oxygen is provided to the follicle by blood vessels around it. VEGF is known to stimulate neovascularisation in response to an FSH stimulus in mouse (Shin et al 2005) and rat follicles (Kuo et al 2011). Furthermore, in primate follicles, VEGF inhibition has been shown to upregulate hypoxia-inducible factor 1a (HIF1a; Duncan et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the ovary, oxygen is provided to the follicle by blood vessels around it. VEGF is known to stimulate neovascularisation in response to an FSH stimulus in mouse (Shin et al 2005) and rat follicles (Kuo et al 2011). Furthermore, in primate follicles, VEGF inhibition has been shown to upregulate hypoxia-inducible factor 1a (HIF1a; Duncan et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The treated cells were compared with control cultures that were incubated under identical conditions, but in the absence of TGF-β1 or IGF-1. After a 24 hour treatment, total RNA was isolated from the HCE B-3 cells using TRIzol as the extraction reagent (Gibco-Invitrogen, Carlsbad, CA, USA) 9. Cells were used at passage five for all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…It is not only involved in the normal physiological processes of ovarian activity, but also involved in the occurrence and development of many ovulatory disorders [11-13]. Numerous factors have been found to regulate VEGF expression, such as hypoxia-inducible factors, cytokines, growth factors and gonadotropins [1, 11, 14-20]. Although numerous studies have shown that inflammatory cytokines are one of the major inducing factors that regulate the expression of VEGF in non-ovarian cells [21-27], whether inflammatory cytokines are involved in regulating FSH-induced VEGF expression in ovarian follicles are still unknown.…”
Section: Introductionmentioning
confidence: 99%